Essais de réduction de la concentration d’un antalgique antiinflammatoire présent dans les eaux en quantité infimes - Benabdallah, mohamed; Djillali, sara (My University, 2024)
The study titled "Essais de réduction de la concentration d’un antalgique anti-inflammatoire présent dans les eaux en quantité infimes" addresses the pressing issue of pharmaceutical pollution, focusing on ibuprofen, a commonly used non-steroidal anti-inflammatory drug (NSAID) found in trace amounts in water bodies. The research highlights the significant environmental impact of pharmaceuticals, introduced through various routes such as industrial discharge, agricultural runoff, and improper disposal of medications. The study employs the adsorption method to reduce ibuprofen concentrations, using activated carbon as the adsorbent. It investigates various factors influencing the adsorption efficiency, including the concentration of ibuprofen, pH levels, temperature, and the surface area and characteristics of the adsorbent. The preparation and characterization of different forms of activated carbon are meticulously detailed, along with the experimental setup and procedures. The research examines adsorption isotherms and kinetics, utilizing models like Langmuir and Freundlich, to describe the adsorption process and determine the best fit for ibuprofen removal. It also discusses the impact of different adsorption parameters such as contact time, adsorbent dosage, and solution pH on the removal efficiency. Through this comprehensive study, the authors emphasize the critical need for effective wastewater treatment systems to address pharmaceutical pollutants, which were not adequately managed by traditional treatment processes. By reducing the concentration of harmful substances like ibuprofen in water, the research aims to protect both environmental and human health, highlighting the broader implications of pharmaceutical waste management in maintaining ecological balance and public safety. Keywords in English: 1. Process Engineering 2. Pharmaceutical products 3. Pollution 4. Water pollution 5. Soil pollution 6. Ibuprofen 7. Adsorption 8. Advanced Oxidation Processes (AOPs) 9. Reverse Osmosis (RO) 10. Biofiltration 11. Activated Carbon Adsorption 12. Environmental Impact 13. Emerging Contaminants 14. Treatment Methods 15. Pharmaceutical Waste 16. Kinetics 17. Adsorption Isotherms 18. Chemical adsorption 19. Physical adsorption 20. Factors influencing adsorption Keywords in French: 1. Génie des procédés 2. Produits pharmaceutiques 3. Pollution 4. Pollution de l'eau 5. Pollution des sols 6. Ibuprofène 7. Adsorption 8. Procédés d'oxydation avancée (AOP) 9. Osmose inverse (OI) 10. Biofiltration 11. Adsorption sur charbon actif 12. Impact environnemental 13. Contaminants émergents 14. Méthodes de traitement 15. Déchets pharmaceutiques 16. Cinétique 17. Isothermes d'adsorption 18. Adsorption chimique 19. Adsorption physique 20. Facteurs influençant l'adsorption
Keywords: Produits pharmaceutiques; Pollution; Pollution de l'eau; Pollution des sols; Ibuprofène; Adsorption; Déchets pharmaceutiques; Isothermes d'adsorption; Adsorption chimique; Adsorption physique